The Effect of Inspiratory Muscle Training on spirometry parameters of Patients with Chronic Obstructive Pulmonary Disease - Khoshkhabar, Mahdi; Mirenayat, Maryam; Abedi, Mohsen; Karimzade, Saba; Rizehbandi, Mahsa; Fakharian, Atefeh (Journal of Clinical Physiotherapy Research, 2020)
Introduction: The present study aimed to investigate the effects of inspiratory muscle training (IMT) on the spirometry parameters of patients with chronic obstructive pulmonary disease (COPD). Materials and methods. In this study, 60 men with COPD referring to Masih Daneshvari Hospital of Tehran were selected and randomly assigned to control (normal rehabilitation) and test (normal rehabilitation with IMT) groups. In addition to standard drug therapy, patients in the test group participated in a 4-week exercise therapy program (for sessions per week) consisting of strength training for the proximal muscles of the upper and lower extremities, aerobic exercises with treadmill, and IMT. The spirometry parameters including FEV1 and FVC were measured before and after the training period. The obtained data were statistically analyzed using the dependent t-test and analysis of covariance at the 0.05 level of significance. Results: The results revealed that IMT significantly improved the FEV1 and FVC in patients with COPD (P<0.05). In addition, the results showed that IMT was more effective than normal rehabilitation in improving the studied variables (P<0.05). Conclusion: It can be generally concluded that respiratory and rehabilitation exercises with an emphasis on inspiratory muscles strengthening can improve the spirometry parameters in patients with COPD. This suggests these patients should benefit from IMT programs. Keywords: Inspiratory Muscle Training, Spirometry Parameters, Chronic Obstructive Pulmonary Disease